A study on prevalence of vitamin D Deficiency among pregnant women attending a tertiary health centre in Rajasthan, India - Yadav, Omesh; Syed, Yasmin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Objective of the study was to study the prevalence of vitamin D deficiency among antenatal women and in relation to parity, BMI, diet and working status. Methods: Prospective study conducted at NIMS Medical College, Jaipur from Dec 2019-July 2021, in the Department of Gynaecology and Obstetrics. It was a hospital based observational study 160 pregnant women were included in the study after obtaining written informed consent. Blood was collected at their first visit itself and 25 (OH) D3 level was tested by Chemiluminescent Immunoassay (CLIA) in hospital lab. And results were analysed. Results: Out of 160 antenatal women, only 12 (07.50%) had sufficient vitamin D levels of 30-100 ng/ml. Mean (SD) vitamin D level in this group was 41.1±10.8. 41 (25.625%) participants had vitamin D insufficiency (20-29 ng/ml) with a mean (SD) of 22.6±2.3 and 107 (68.875%) participants had vitamin D deficiency with serum level <20 ng/ml with a mean (SD) value of 13.8±3.9. Vitamin D deficiency and insufficiency together (vitamin D <30 ng/ml) constituted 92.50% and the mean (SD) was 16.2±5.6. Among vitamin D deficient group, 26 (16.25%) were having vitamin D level <10 ng/ml with a mean of 8.1±1.3. Conclusions: There is high prevalence of vitamin D insufficiency and deficiency among antenatal women attending the OPD in NIMS Medical College and Hospitals in Rajasthan region. Since vitamin D has crucial role in maternal and foetal health outcomes, it is of utmost importance to correct this deficiency in pregnancy.